Effect of failure/success feedback and the moderating influence of personality on reward motivation. Issue 3 (2nd April 2016) - Anand, Deepika; Oehlberg, Katherine A.; Treadway, Michael T.; Nusslock, Robin
Abstract : While motivation to pursue goals is often assumed to be a trait-like characteristic, it is influenced by a variety of situational factors. In particular, recent experiences of success or failure, as well as cognitive responses to these outcomes, may shape subsequent willingness to expend effort for future rewards. To date, however, these effects have not been explicitly tested. In the present study, 131 healthy individuals received either failure or success feedback on a cognitive task. They were then instructed to either ruminate or distract themselves from their emotions. Finally, they completed the Effort Expenditure for Rewards Task, a laboratory measure of reward motivation. Results indicate that participants who received failure feedback relied more strongly on the reward magnitude when choosing whether to exert greater effort to obtain larger rewards, though this effect only held under conditions of significant uncertainty about whether the effort would be rewarded. Further, participants with high levels of trait inhibition were less responsive to reward value and probability when choosing whether to expend greater effort, results that echo past studies of effort-based decision-making in psychological disorders.